2019
DOI: 10.1002/cctc.201901196
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing FeNC Materials as Electrocatalysts for the CO2 Reduction Reaction: Heat‐Treatment Temperature, Structure and Performance Correlations

Abstract: The direct CO 2 electrochemical reduction reaction (CO2RR) into carbon-based chemicals has attracted tremendous attention as a sustainable process for CO 2 utilization. The viability of the process, however, is contingent on finding efficient catalysts based on earth abundant elements. Carbon-based solid catalyst materials doped with nitrogen and transition metals (MÀ NÀ C) have emerged as a cost-efficient alternative for the direct electrochemical reduction of CO 2 into CO. These materials contain different N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…This process results in inhomogeneous materials containing a variety of chemical functionalities, including metal centers coordinated to nitrogen in MN x moieties, similar to those on metal macrocycles. 25…”
Section: Introductionmentioning
confidence: 99%
“…This process results in inhomogeneous materials containing a variety of chemical functionalities, including metal centers coordinated to nitrogen in MN x moieties, similar to those on metal macrocycles. 25…”
Section: Introductionmentioning
confidence: 99%
“…To further study the correlations between the reaction activity and material structure, González‐Cervantes et al 68 prepared Fe‐SACs on nitrogen‐doped carbon by the pyrolysis method. By monitoring the reaction performance on the catalysts treated under different pyrolysis temperature, they observed a clear impact on the catalytic performance.…”
Section: M‐sacs For Co2rrmentioning
confidence: 99%
“…These results indicated that FeN x moieties played a predominant role in the reaction. However, an overall current density decreased, which resulted from the smaller surface area and micropore area caused by the high temperature treatment 68 …”
Section: M‐sacs For Co2rrmentioning
confidence: 99%
See 2 more Smart Citations